A dual-process perspective on the disparities between designers' intention and consumers' impression of new products. (10th July 2022) - Haug, Anders
This paper investigates how designers avoid that their product designs elicit unwanted impressions for the consumers encountering these. This is done by taking a basis in dual-process theory, a psychological theory of how thoughts arise. Using this theory, a model of the process, in which impressions of new products are formed, is constructed. The model is investigated through interviews of 15 consumer product designers. Analysis of these interviews identifies 24 distinct types of mental processes that may cause disparities between designers' intentions and consumers' impressions when they encounter new products. Finally, these 24 causes of disparities are converted into a checklist that may be applied in the design of new products.